2016
DOI: 10.1002/bit.25893
|View full text |Cite
|
Sign up to set email alerts
|

An orbital shear platform for real‐time, in vitro endothelium characterization

Abstract: Electrical impedance techniques have been used to characterize endothelium morphology, permeability, and motility in vitro. However, these impedance platforms have been limited to either static endothelium studies and/or induced laminar fluid flow at a constant, single shear stress value. In this work, we present a microfabricated impedance sensor for real-time, in vitro characterization of human umbilical vein endothelial cells (HUVECs) undergoing oscillatory hydrodynamic shear. Oscillatory shear was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 87 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…Starting with the work of Berson et al [ 35 ], numerical models of the orbital shaker system [ [30] , [31] , [32] , 34 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] have shown that WSS magnitude fluctuates with time, more so towards the edge of the well than at its centre, and that TAWSS is also greater towards the edge. Additionally, the direction of the instantaneous WSS vector rotates evenly through 360° at the centre of the well during each orbit whereas at the edge, vectors tend only to switch between forward and backward orientations along a line that is approximately parallel to the wall.…”
Section: Characterisation Of Flow In Swirling Wellsmentioning
confidence: 99%
“…Starting with the work of Berson et al [ 35 ], numerical models of the orbital shaker system [ [30] , [31] , [32] , 34 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] have shown that WSS magnitude fluctuates with time, more so towards the edge of the well than at its centre, and that TAWSS is also greater towards the edge. Additionally, the direction of the instantaneous WSS vector rotates evenly through 360° at the centre of the well during each orbit whereas at the edge, vectors tend only to switch between forward and backward orientations along a line that is approximately parallel to the wall.…”
Section: Characterisation Of Flow In Swirling Wellsmentioning
confidence: 99%
“…It can be used to measure a variety of cellular properties, e.g., behavior under flow [ 52 ]. Another setup is the combination of a small impedance chip with an orbital shaker to produce oscillatory shear, which allows the measurement of trans-endothelial resistance against varying shear stress conditions [ 53 ]. Furthermore, microfluidic chips, also known as “organ-on-a-chip” technology, is a further advanced form of in vitro systems, which may contribute to our understanding of EC responses to hemodynamics [ 54 ] (reviewed in [ 55 , 56 ]).…”
Section: In Vitro Systems To Model Flow Dynamics and Endothelial Wall Shear Stress (Wss)mentioning
confidence: 99%
“…Moreover, extrapolation of animal data to human conditions has been frustratingly controversial, particularly for complex diseases afflicting dynamic microenvironments prevalent with mechanochemical stimuli such as blood flow and inflammatory cytokines 13 . Overcoming traditional in vitro models that predominantly rely on static culture of vascular endothelial cells, current advanced in vitro studies on endothelial mechanotransduction have taken the magnitude and direction of OSS into consideration to complement existing animal model research 3 , 4 , 8 , 9 , 14 16 . The frequencies typically associated to be characteristic of disease-causing OSS are based on measured physiological values in vivo ; this value is about 5 Hz in mice, whereas in humans this level drops to approximately 1 Hz 3 , 10 , 17 .…”
Section: Introductionmentioning
confidence: 99%